A Two Year Observation on Trend of Primary Glomerulonephritis in A Tertiary Care Hospital of Bangladesh - Samad, Tabassum; Haque, Wasim Md Mohosin Ul; Rahim, Muhammad Abdur; Ananna, Mehruba Alam; Iqbal, Sarwar (Bangladesh Journal of Medicine, 2016)
Aim: Glomerulonephritis remains the most probable underlying cause of end stage renal disease of uncertain aetiology in many developing countries, including Bangladesh. The pattern of glomerular disease varies widely from country to country. In Bangladesh, the incidence and histological pattern of glomerulonephritis is inadequately described. We performed a study, aiming to determine pattern of primary glomerulonephritis in a tertiary care hospital of our country. Material & Methods: It was a cross-sectional hospital based prospective study conducted at BIRDEM general hospital starting from from July 2013 to June 2015. It included all patients with primary glomerulonephritis and who underwent native kidney biopsy. Result: Total 67 biopsy were performed and among them primary glomerulonephritis was 42. Female and male ratio was 1.3:1 and mean age was 42.73±14 (14-75) years. Indications of biopsy were proteinuria (>1gm/day) and unexplained acute kidney injury. The commonest histopathological pattern in primary glomerulonephritis was membranoproliferative glomerulonephritis 33.33% (14/ 42) followed by mesangial proliferative glomerulonephritis 30.95% (13/42). Only three (7%) patient required blood transfusion for post biopsy bleeding. No one required nephrectomy. Conclusion: In conclusion, mesangial proliferative and membranoproliferative glomerulonephritis are the two most common causes of primary glomerulonephritis. Nephrotic range proteinuria was the main indication of biopsy. Post biopsy complication was negligible. Creation of a national renal registry is essential for obtaining more specific epidemiological data. Bangladesh J Medicine Jul 2016; 27(2) : 68-70